2010
DOI: 10.1590/s1413-70542010000100028
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do cultivo de Pleurotus sajor-caju (fries) sing. sobre o resíduo de algodão da industria têxtil para a produção de cogumelos e para alimentação animal

Abstract: RESUMOO resíduo proveniente do beneficiamento do algodão em lixadeiras na indústria têxtil é um material rico em lignocelulose, tem baixa digestibilidade e é pobre em proteínas e minerais, o que dificulta seu uso 'in natura' na alimentação de ruminantes. Neste tarbalho, objetivou-se avaliar a produtividade e eficiência biológica deste resíduo de algodão na produção do cogumelo comestível Pleurotus sajor-caju e avaliar as alterações promovidas no resíduo para alimentação de ruminantes. Foram realizados 5 tratam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 12 publications
2
4
0
Order By: Relevance
“…According to Castro (2003), reductions in NDF and ADF contents in the final (residual) substrate are expected, because fungi have an enzymatic ability to degrade components of the cellular wall that are present in the raw material of vegetable origin. These results agree with several other works that also reported reductions in NDF and ADF fractions in substrates treated by fungi (Belewu and Belewu, 2005; Gonçalves et al , 2010). …”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…According to Castro (2003), reductions in NDF and ADF contents in the final (residual) substrate are expected, because fungi have an enzymatic ability to degrade components of the cellular wall that are present in the raw material of vegetable origin. These results agree with several other works that also reported reductions in NDF and ADF fractions in substrates treated by fungi (Belewu and Belewu, 2005; Gonçalves et al , 2010). …”
Section: Resultssupporting
confidence: 93%
“…According to Andrade et al (2010), both holocellulose (hemicellulose and cellulose set) and lignin contain carbon, hydrogen, and oxygen and serve as an energy source for fungal growth, a fact that explains their reduction along the cultivation cycle. Gonçalves et al (2010) report that the significant reduction in lignin is related to the efficiency of the fungi to degrade that structure. In addition, sometimes, they degrade lignin rather than cellulose and hemicellulose.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the fiber content, there was a significant increase after the mushroom myceliation in the three bioproducts analyzed. Gonçalves et al (2010) found a similar behavior with increased fiber content in the colonized substrate. According to them these results can be explained due to the production of different enzymes during vegetative and reproductive stages of mushrooms, and the enzymes responsible for degradation of cellulose are secreted only in the reproductive phase.…”
Section: Chemical Compositionsupporting
confidence: 57%
“…Thus, there was no significant reduction in fiber content in the bioproducts samples since fungi do not reach reproductive phase. Still, in the study of Gonçalves et al (2010), the fiber contents decrease after production and harvesting of mushrooms. Being a potential source of dietary fibers, mushrooms raise the possibility of its inclusion in the highly competitive market of fiberenriched food products, which seriously demands the exploration of alternative source and preparation methods of dietary fibers (Fernandes et al, 2015).…”
Section: Chemical Compositionmentioning
confidence: 94%
“…Much research has been carried out on numerous physicochemical methods for treating OMWW, alone or combined, such as oxidation, filtration, centrifugation, flocculation, incineration, coagulation, ultrafiltration, reverse osmosis, ozonation, or photolysis. Many of these approaches are efficient for pollutant removal-namely monophenolic compounds and high organic charge-and consequently quite useful as pretreatment methods, but they are expensive and do not generate valuable sub-products [11]. Furthermore, since conventional olive mill waste-treatment methods have proven to be inadequate and ineffective for removing OMWW pollutants, several studies have been carried out in order to use this waste as a renewable resource and to transform OMWW from a pollutant to organic fertilizer, agricultural water source, or green fuel [12].…”
Section: Introductionmentioning
confidence: 99%